Language identity and its context policies - ASHRAPOVA, A; LITVINENKO, E; SHAKIROVA, D (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Formation of the civil nation is the most important task for any state which is related to all-civil identity. Russia faces serious ethnocultural problems connected to the formation of both linguistic identity and civil identity. At the theoretical level, this research investigates the question of important factors of balanced language policy in the multinational states and the preservation of language identity. The linguistic dimension of globalization takes into account the constructive language policy with regard to languages of national minorities and destructive forms of language interaction caused by economic and political dependence on more developed states. RESUMEN La formación de la nación civil es la tarea más importante para cualquier estado relacionado con la identidad totalmente civil. Rusia enfrenta serios problemas etnoculturales relacionados con la formación de la identidad lingüística y la identidad civil. A nivel teórico, este trabajo investiga la cuestión de los factores importantes de una política lingüística equilibrada en los estados multinacionales y la preservación de la identidad lingüística. La dimensión lingüística de la globalización tiene en cuenta la política lingüística constructiva con respecto a las lenguas de las minorías nacionales y las formas destructivas de interacción lingüística causadas por la economía y la política.